Revitalisasi Danau Pading: Aktualisasi Partisipasi Pemuda dalam Pengembangan Desa Wisata di Desa Perlang, Provinsi Kepulauan Bangka Belitung - Suntara, Reza Adriantika; Pasaribu, Waldimer (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
The Bangka Belitung Islands Province has long been known as one of the world's largest tin producers. Currently, many former tin mining areas produce holes or kulongs and are left gaping without any responsibility from mining companies. One of them is located in Perlang Village, Central Bangka Regency. Then, on the initiative of young people who were members of the tourism awareness group (Pokdarwis), this area was transformed into a tourist destination which was then much sought after by tourists, known as Lake Pading. This article discusses the actualization of civic participation carried out by young people in increasing the potential of tourist villages in Perlang Village. This research uses a qualitative approach with descriptive methods. Data collection was carried out through a process of observation, interviews and document study. The results of this research show that youth participation in the revitalization of Pading Lake through voluntary cooperation has produced good results with increasing tourist visits and several awards being won. The actions taken by these young people are in line with the concept of civic participation, a citizenship concept which indicates the contribution of citizens in creating positive and beneficial social change for the wider community. The limitation of this research is that it does not look at the sustainability of revitalization efforts and citizen participation in the long term. Revitalization efforts are only the first step in civic participation, so it is hoped that future research can address these limitations.